EFEKTIVITAS BERKUMUR LARUTAN PROBIOTIK TERHADAP PENINGKATAN pH SALIVA (STUDI LITERATUR) (Jurnal Kesehatan Siliwangi, 2021)
Saliva is a complex oral fluid consisting of a mixture of secretions from the salivary glands present in the oral cavity. Saliva is mostly produced while eating. Food can cause saliva to be acidic or alkaline. Saliva acts as a buffer system to maintain a neutral pH. The acidity level of neutral salivary pH is at number 7. Bacterial growth occurs at the optimum salivary pH range (4.5-5.5) which will facilitate the growth of Streptococcus mutants bacteria which is the bacteria that causes caries. The degree of acidity (pH) of saliva can increase the occurrence of remineralization which will reduce the occurrence of caries. This study aimed to analyze the effectiveness of gargling probiotic solution on increasing salivary pH. This type of research is a literature study. The method of data collection is by taking data in libraries or official writings published by the government and other institutions, both books and digital. The results of the literature review found that there was a significant difference in saliva pH before and after rinsing probiotic solutions, namely the salivary pH has increased towards alkaline.